Dificuldades de aprendizagem: implicações da família e da escola - Antunes, Márcia Elisa da Silva (Universidade do Vale do Rio dos Sinos, 2010)
Learning disabilities are a complex phenomenon which reveals itself in the learning process of children and teenagers. In adolescence, they tend to be exacerbated due to the common characteristics of this life stage; not only affecting the student?s academic performance, but also aspects of his/her personal and social life. By and large, learning disabilities emerge as a symptom related to the family and social environment in which he/she is inserted. Having this in mind, this thesis aims to deepen our understanding of this phenomenon, as it gives voice to different characters of teenagers? family and school environment. Section 1 of this thesis presents a systematic review of the literature about learning disabilities in adolescence in dada from national and international contexts elaborated from 2005 to 2009. Section II presents a qualitative study, guided by multiple case studies methodology, about the perception of teenagers and their mothers regarding learning disabilities. It has been verified that their understandings of this phenomenon are limited as they attribute the difficulties to inherent characteristics of the teenagers or of their teachers. The third section describes the data of research reports through the identification of analytical categories in the speech of adolescents, their mothers, their teachers and other professionals of the schools where the research subjects study.
Keywords: Dificuldades de aprendizagem; Adolescentes; Família; Escola; ACCNPQ::Ciências Humanas::Psicologia